Analyzing the Influence of Investment and Government Expenditure on Regional Economic Growth: Evidence from Bengkulu Province (2003-2023) - Esti Pasaribu; Apriyanti, Cikit (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study examines the influence of investment and government expenditure on economic growth in Bengkulu Province, based on time series data from the Badan Pusat Statistik (BPS) of Bengkulu Province for the period 2003–2023. The research method employs multiple linear regression with economic growth (GRDP) as the dependent variable, and investment and government expenditure as independent variables. The results indicate that statistically, investment and government expenditure have no significant effect on economic growth in Bengkulu. However, the GRDP variable itself has a positive and significant effect on economic growth, with a coefficient of 0.281. The study concludes that the increase in investment and government spending has not yet had a tangible impact on accelerating Bengkulu’s economic growth within the model used. Therefore, further in-depth studies and supportive policies are needed so that investment and government expenditure can effectively contribute to regional economic growth. The research also discusses theories of investment, government expenditure, and economic growth, as well as reviews previous studies on the impact of investment and government spending on economic growth in other regions, which show varied results.